Editorial: Revisiting the role of business, technical and financial services in fostering rural entrepreneurship - Donovan, J.; Hellin, Jonathan; Stoian, D. (Practical Action Publishing, 2017)
Over the past 15 or so years authors in Enterprise Development and Microfinance (EDM) have written extensively about the design and implementation of microfinance and its use by the poor, whether to respond to shocks and changing contexts, invest in education, or advance livelihood goals (Figure 1 overleaf). Coverage has ranged from the specifics of designing microfinance schemes, access to them by the poorest, and their impact on wellbeing and poverty. While the debate on microfinance is far from over, it is true that discussions have been more concerned with managing, saving, borrowing, and moving money, than about building viable businesses. Business development involving the poor, which in many cases focuses on rural small and medium enterprises (SMEs), requires us to address the demand for a range of services which, taken together, enhance the capacities of rural SMEs. Such services need to be affordable and reliable, and address the productive and business needs of SMEs, from small-scale processors to multi-tiered agricultural cooperatives. The issues are complex with lingering questions about how different types of service providers, from government agencies and NGOs to various private sector agents, can better design their services; and how, through adequate delivery mechanisms, the capacity and willingness of SMEs to employ such services can be strengthened. In this Editorial, we discuss some of the key issues for advancing rural entrepreneurship via improved services and provide an outlook for future discussions.